Development of zinc alkyl/air systems as radical initiators for organic reactions1. Issue 5 (20th May 2015) - Kubisiak, Marcin; Zelga, Karolina; Bury, Wojciech; Justyniak, Iwona; Budny-Godlewski, Krzysztof; Ochal, Zbigniew; Lewiński, Janusz
<x xml:space="preserve">Abstract</x> A novel organozinc initiator with a clear mechanistic signature for organic radical reactions has been developed.